Cancer theranostics - Chen, Xiaoyuan; Wong, Stephen (Elsevier/Academic Press, 2014)
Aiding researchers seeking to eliminate multi-step procedures, reduce delays in treatment and ease patient care, Cancer Theranostics reviews, assesses, and makes pertinent clinical recommendations on the integration of comprehensive in vitro diagnostics, in vivo molecular imaging, and individualized treatments towards the personalization of cancer treatment. Cancer Theranostics describes the identification of novel biomarkers to advance molecular diagnostics of cancer. The book encompasses new molecular imaging probes and techniques for early detection of cancer, and d.